Risk And Return For The Dollar-Cost Averaging (Dca) Versus Lump-Sum (Ls) Strategy On The Market Portfolio Of Stocks Listed On The Kuala Lumpur Stock Exchange (Klse) - CHOW, FATT VING (2004)
The purpose of this study was to examine the risk and return profile of the Dollar - Cost Averaging versus Lump-Sum investment strategies in the market portfolio of stocks listed on the Kuala Lumpur Stock Exchange (KLSE). KLSE is weak form efficient and historical prices cannot be used to predict future prices. Uncertainties in the macro economic and global environment have increased volatility in the Malaysian stock market for the past decade.